Weight Gain Prevention for College Freshmen: Comparing Two Social Cognitive Theory-Based Interventions with and without Explicit Self-Regulation Training - Elizabeth A. Dennis; Kerry L. Potter; Paul A. Estabrooks; Brenda M. Davy (Journal of Obesity)
The college transition represents a critical period for maintaining a healthy weight, yet intervention participation and retention represent significant challenges. The objective of this investigation was to evaluate the preliminary efficacy and acceptability of two interventions to prevent freshman weight gain. One intervention provided opportunities to improve outcome expectations and self-efficacy within a social cognitive theory framework (SCT), while the other targeted the same variables but focused on explicit training in self-regulation skills (SCTSR). Methods. Freshmen (n=45) aged >18 years were randomized to a 14-week intervention, SCT or SCTSR; both included online modules and in-class meetings. Of the 45 students randomized, 5 withdrew before the classes began and 39 completed pre- and posttesting. Primary outcomes included body weight/composition, health behaviors, and program acceptability. Analyses included independent sample t-tests, repeated measures ANOVA, and bivariate correlational analyses. Results. Body weight increased over the 14-week period, but there was no group difference. Percent body fat increased in SCTSR but not SCT (mean difference: SCTSR, +1.63 ± 0.52%; SCT, −0.25 ± 0.45%; P=0.01). Class attendance was 100% (SCTSR) and 98% (SCT); SCTSR students (>50%) remarked that the online tracking required “too much time.” Conclusions. The intervention was well received, although there were no improvements in weight outcomes.